Effect of the Osmotic Pressure of the Growth Medium on fabB Mutants of Escherichia coli - Broekman, J. H. F. F. (1974)
Temperature-sensitive, unsaturated fatty acid (fabB) auxotrophs of Escherichia coli can grow at the restrictive temperature in the absence of unsaturated fatty acid in a medium with a high osmotic pressure. If a mutant culture was starved for unsaturated fatty acids and harvested just before the lysis started, the fatty acid composition of the cells was the same as that of cells grown until late log phase in a high-osmotic medium. Evidence is presented that the in vivo unsaturated fatty acid biosynthesis is significantly increased in a high osmotic medium. The increase is probably due to a partial activation of the temperature-sensitive fabB product. Besides the stimulation of the temperature-sensitive fabB product, a minimal osmotic pressure of the medium appeared to be necessary to allow growth of cells containing lipids with a changed fatty acid composition. fabA mutants are unable to grow in a high-osmotic medium in the absence of unsaturated fatty acids. No increase in the in vivo unsaturated fatty acid biosynthesis could be detected in the temperature-sensitive fabA mutants.